Pendampingan Menghafal AlQuran melalui Metode Talaqqi di TPQ Masjid Muhajirin Padang Besi Kota Padang - Aziz, Ahmad; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2024)
This service aims to improve the ability to memorize the Alquran students at the TPQ Muhajirin Mosque using the Talaqqi method. The method that the author uses in this mentoring is the ABCD (Asset Based Community Driven Development) method, which is a method to increase the active role of all children, it is the children who play a more important role in achieving Al-Quran education where ustad and ustadzah act as motivation so that children are able to develop their potential with the same abilities. owned. The Talaqqi method that will be implemented consists of two cycles. Each cycle consists of three steps, namely planning, implementation, and reflection. Data is collected using techniques, tests, and documentation. The results of the study showed that the student's ability to read the Alquran in pre-action still did not meet the minimum completeness criteria. In cycle 1, the ability to read the Alquran of students who were able to meet the criteria only 2 students (makharijul huruf), 1 student (sifatul huruf), and 2 students (ahkamul makharijul huruf), after learning was carried out in cycle 2 it increased so that those who were able to meet the criteria became 8 santri (makharijul huruf), 7 santri (sifatul huruf), and 5 santri (ahkamul huruf) santri. These results indicate that the learning outcome scores have exceeded the predetermined criteria limits. The response from the application of this method among students was enthusiastic and the students' interest in studying and memorizing according to the rules of recitation increased.